2010
DOI: 10.1063/1.3366710
|View full text |Cite
|
Sign up to set email alerts
|

Strong competition between the δl and δTc flux pinning mechanisms in MgB2 doped with carbon containing compounds

Abstract: The transport and magnetic properties of 10 wt % malic acid and 5 wt % nanocarbon doped MgB2 have been studied by measuring the resistivity (ρ), critical current density (jc), connectivity factor (AF), irreversibility field (Hirr), and upper critical field (Hc2). The pinning mechanisms are studied in terms of the collective pinning model. It was found that both mean free path (δl) and critical temperature (δTc) pinning mechanisms coexist in both doped MgB2. For both the malic acid and nanocarbon doped samples,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…For δT c pinning, ∝ − + ( ) ( ) In the single-vortex-pinning region the following B sb temperature dependence can be obtained [17]: where the parameter ν = 0.67 and 2 for δT c and δℓ pinning, respectively. It was found that there is no agreement between the experimental data for the doped MgB 2 and equation (3) with ν = 2 or 0.67 [15,18], and that strongly suggests that the δT c and the δℓ pinning mechanisms coexist in our samples. The δℓ and δT c pinning mechanisms are the main pinning mechanism.…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations
“…For δT c pinning, ∝ − + ( ) ( ) In the single-vortex-pinning region the following B sb temperature dependence can be obtained [17]: where the parameter ν = 0.67 and 2 for δT c and δℓ pinning, respectively. It was found that there is no agreement between the experimental data for the doped MgB 2 and equation (3) with ν = 2 or 0.67 [15,18], and that strongly suggests that the δT c and the δℓ pinning mechanisms coexist in our samples. The δℓ and δT c pinning mechanisms are the main pinning mechanism.…”
Section: Resultsmentioning
confidence: 72%
“…Partial doping substitution and Mg deficiency are the two main reasons for the T c fluctuation, while the mean free path fluctuation, and hence the δℓ pinning, is caused by the intergrain boundaries and interagrain inclusions. For MgB 2 superconductor, it has been shown that δT c pinning is dominant in undoped MgB 2 samples, while both δT c and δℓ pinning mainly coexist in carboncontaining doped MgB 2 bulk samples [15,18,24].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the irradiation method can improve J c in MgB 2 , but it reduces T c values significantly (by more than 20 K in some cases) [23][24][25][26][27]. Correspondingly, the chemical doping and irradiation methods can also change the nature of the pinning mechanism in MgB 2 [24,[28][29][30]. The determination of J c and the flux pinning mechanism under hydrostatic pressure is also an important step to probe the mechanism of superconductivity in more detail in MgB 2 .…”
mentioning
confidence: 99%